(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
This paper examines the structure of some ‘classics’ books of 20th Century Literature employing the Warburghian iconology method. Books, in fact, combine a concrete object with visual, textual and paratextual elements (visual and verbal) joined in a whole that is both an aesthetic and a communicative object.